Failure Investigation of Plastic Shredding Machineâs Flange Coupling Based on Mechanical Analysis - Christianto, Theo
Plastic shredding machine supports plastic waste recycling program. The small sized particles simplifies storing, packaging, and transportation of plastic waste. In order to obtain the small sized particles, plastic waste is fed into the shredding machine. The problem with the prototype of the shredding machine is that the flange coupling broke as we fed thick plastic bottle into the machine in the preliminary trial. The coupling connects the shaft of the gearbox to the shaft of the cutter. The focus of this undergraduate thesis is on failure investigation of the flange coupling. Due to time limitation, failure analysis will be confined to mechanical analysis using finite element method or FEM. Stresses as the result of FEM will be compared to material’s strength. Conclusion will be drawn based on the above comparison. Visual inspection of the fracture surface of the broken coupling indicates that brittle failure has occurred. This also confirms that the coupling was made from cast steel. FEM result indicates that the largest stress occurs at the corner of the keyway slot. Material’s strength was estimated from Brinell hardness testing utilizing standard transformation formula. Upon comparing the maximum stress and material’s strength, it is revealed that the coupling fails due to overloading of brittle materials. In order to prevent the above failure, coupling needs to be redesigned by changing the material using ductile materials with higher strength